2016
DOI: 10.1111/jth.13214
|View full text |Cite
|
Sign up to set email alerts
|

Global public awareness of venous thromboembolism: comment

Abstract: We read with interest the article by Wendelboe et al. [1], in which the authors reported a low public awareness of venous thromboembolism (VTE). In their large survey of > 7000 respondents from the general population of nine countries, 68%, 44% and 54% of the respondents were aware of the terms 'thrombosis, deep vein thrombosis (DVT) and pulmonary embolism (PE)', respectively. The level of awareness was lower than that for other serious diseases such as heart attack and stroke (88% and 85%, respectively). In p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Similarly, a previous Japanese study reported that the mortality rate attributable to PE was 14% [ 6 ]. In about 25% of the patients with PE, the first sign/symptom of PE is death [ 25 ], and more than 10–13.5% of deaths occur within 1 h of onset of PE [ 7 , 8 ]. Death in such a short time after onset may be difficult to avoid, but if the risk is properly assessed and if the onset of PE can be predicted, a prompt response may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a previous Japanese study reported that the mortality rate attributable to PE was 14% [ 6 ]. In about 25% of the patients with PE, the first sign/symptom of PE is death [ 25 ], and more than 10–13.5% of deaths occur within 1 h of onset of PE [ 7 , 8 ]. Death in such a short time after onset may be difficult to avoid, but if the risk is properly assessed and if the onset of PE can be predicted, a prompt response may be possible.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Drs Aggarwal and Rickles for their comments and commend them on their efforts to assess the awareness of cancer‐associated venous thromboembolism (VTE). Their findings are remarkably consistent with the results of our global awareness survey .…”
mentioning
confidence: 99%